Dry and real shooting in biathletes: postural and aiming control - Zoppirolli, C.; Bortolan, L.; Mezzaro, E.; Schena, F.; Pellegrini B. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Shooting performance relies on hold stability, postural balance and triggering clearness in modern biathlon. World-class athletes perform around 22,000 shots/year, with dry shooting (i.e. without ammunition, typically used for training) taking more than 50% of total shots. Here, we aimed to evaluate postural sway and aiming parameters during dry and real shooting.